Resource utilisation among patients transferred for intracerebral haemorrhage. Issue 4 (28th November 2019) - Zachrison, Kori Sauser; Aaronson, Emily; Mahmood, Sadiqa; Rosand, Jonathan; Viswanathan, Anand; Schwamm, Lee H; Goldstein, Joshua N
Abstract : Background: Patients with intracerebral haemorrhage (ICH) are frequently transferred between hospitals for higher level of care. We aimed to identify factors associated with resource utilisation among patients with ICH admitted to a single academic hospital. Methods: We used a prospectively collected registry of consecutive patients with primary ICH at an urban academic hospital between 1 January 2005 and 31 December 2015. The primary outcome was use of either intensive care unit (ICU) admission or surgical intervention. Logistic regression examined factors associated with the outcome, controlling for age, sex, Glasgow coma score (GCS) and ICH score. Results: Of the 2008 patients included, 887 (44.2%) received ICU stay or surgical intervention. These patients were younger (71 vs 74 years, p<0.001), less often white (83.9% vs 89.3%, p<0.001), had lower baseline GCS (12 vs 14, p<0.001) and more frequently had intraventricular haemorrhage (58.6% vs 43.4%, p<0.001). Factors independently associated with ICU stay or surgical intervention were age >65 years (OR 0.38, 95% CI 0.21 to 0.69), GCS <15 (1.23, 95% CI 1.01 to 1.52) and ICH score >0 (OR 2.23, 95% CI 1.70 to 2.91). Conclusion: Among this cohort of primary patients with ICH, GCS of 15 and ICH score of 0 were associated with less frequent use of ICU or intervention. These results should be validated in a larger sample but may be valuable for hospitals considering which patients with ICH could safely remain at the referring facility.